2020
DOI: 10.3390/cells9092102
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Enhanced Cancer Immunotherapy: Immunology Encounters Nanotechnology

Abstract: Cancer immunotherapy utilizes the immune system to fight cancer and has already moved from the laboratory to clinical application. However, and despite excellent therapeutic outcomes in some hematological and solid cancers, the regular clinical use of cancer immunotherapies reveals major limitations. These include the lack of effective immune therapy options for some cancer types, unresponsiveness to treatment by many patients, evolving therapy resistance, the inaccessible and immunosuppressive nature of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 113 publications
0
34
0
Order By: Relevance
“…As we all know, nanomedicine is the medical application of nanotechnology. At present, the use of nanotechnology is becoming more and more popular, and it affects more and more scientific fields [61][62][63][64][65][66]. Richard Feynman introduced the concept of nanoscale particles to the world in 1959 [67,68].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…As we all know, nanomedicine is the medical application of nanotechnology. At present, the use of nanotechnology is becoming more and more popular, and it affects more and more scientific fields [61][62][63][64][65][66]. Richard Feynman introduced the concept of nanoscale particles to the world in 1959 [67,68].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…In contrast, cancer cells are not affected by miRNA-mediated p53 inhibition because miRNA-30d only has negligible effects on mutated p53, putatively due to its high stability [167,168]. Besides CAFs, tumor-associated macrophages (TAMs), as myeloid derived suppressor cells, contribute to an immunosuppressive microenvironment and support tumor growth as they are a source of immunosuppressive cytokines (e.g., CCL17, CCL18 and CCL22) and tumor promoting growth factors (VEGF-A, TNF-α) [159,[169][170][171]. They stimulate the shift of anti-tumor CD8+ T cells towards immunosuppressive regulatory T cells, which favors immune tolerance and thus act as tumor-promoting agents [172].…”
Section: The Role Of P53 In the Tumor Microenvironmentmentioning
confidence: 99%
“…They stimulate the shift of anti-tumor CD8+ T cells towards immunosuppressive regulatory T cells, which favors immune tolerance and thus act as tumor-promoting agents [172]. In CRC, TAMs possess an intricate role, as their distribution towards the tumor might increase or hinder tumor growth [169]. High numbers of CD68+ TAMs in the invasive front were associated with favorable outcome, while other reports indicated that intratumoral CD68+ TAM counts were related with tumor penetration, lymph node metastasis and advanced stages of colorectal cancer [173][174][175].…”
Section: The Role Of P53 In the Tumor Microenvironmentmentioning
confidence: 99%
“…Recent decades have witnessed the huge progress of employment of nanotechnology in cancer therapy. Except for the tumor cells, nano-based DDSs can be designed as demand to accurately target TME elements and remodel the TME for tumor regression [ 11 ]. Owing to their unique properties, multifunctional CNT-based nano DDSs have shown outstanding ability in targeting the components of TME [ 110 ].…”
Section: Carbon Nanotubes In Cancer Treatmentmentioning
confidence: 99%
“…Nanobiotechnology has emerged as a novel treatment opportunity against cancer in recent decades. The employment of nano-based drug delivery system (DDS) opened a new avenue to integrate multiple anticancer agents in one platform for more efficacious therapeutic outcome with reduced side effects and enhanced targeting ability [ 11 – 13 ]. Due to their unique potential for passive targeting through enhanced permeability and retention (EPR), high surface area for drug loading and modification, and prolonged plasma half-life, nanomedicine possesses numerous benefits over the conventional therapeutic modalities [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%